Cards, Cabinets, and Compression in Early Stock Photography. (Information & Culture, 2021)
Using the case study of 1920s stock photography pioneer H. Armstrong Roberts, this article argues for a historical perspective on the iconomy , or the cultural condition in which images circulate according to market logics. The article argues that compression is a predigital cultural technique that coordinates physical, technical, and narrative structures. Using custom-cut cards, contact prints, a ready-made card catalog system, and an original subject-based alphanumeric ordering system, Roberts produced an analog image database that compressed his visual inventory into discrete bits of information, reflecting a broader conception of the image as alienable content and creating a new commercial aesthetic.